Microstructure and luminescence properties of the high pressure high temperature sintered AlN–TiN ceramics. Issue 12 (15th June 2021) - Kudyakova, Valeriya S.; Leonidov, Ivan I.; Chaikin, Dmitry V.; Shishkin, Roman A.; Zamyatin, Dmitry A.; Weinstein, Ilya A.
Abstract: Composite ceramics of titanium nitride grains incorporated in an aluminium nitride matrix have been synthesized by high pressure high temperature treatment of a mechanical mixture of AlN–TiN (3 mol % TiN) powders. The microstructure of the samples analysed by means of electron beam microanalysis and Raman spectroscopy shows that the formation of cubic AlN in the composite begins near titanium nitride grains. The areas of mixed chemical composition, which can be assigned to the formation of the solid solutions Al1−x Tix N, have been observed at the phase interfaces. The luminescence properties of AlN–TiN ceramics have been considered focusing on the choice of high pressure and high temperature treatment conditions. Three main components at 2.0 eV, 2.4 eV and 3.1 eV are revealed in the cathodoluminescence spectra analysed quantitatively. The observed emission originates from the radiative transitions with participation of valence band states, oxygen-vacancy centres (VAl –ON ), nitrogen vacancies VN, and shallow donors which form a complex system of energy levels in the bandgap of the wurtzite-type AlN.